Runtime latency detection and analysis. (18th February 2016) - Desfossez, Julien; Desnoyers, Mathieu; Dagenais, Michel R.
Summary: Detecting latency‐related problems in production environments is usually carried out at the application level with custom instrumentation. This is enough to detect high latencies in instrumented applications but does not provide all the information required to understand the source of the latency and is dependent on manually deployed instrumentation. The abnormal latencies usually start in the operating system kernel because of contention on physical resources or locks. Hence, finding the root cause of a latency may require a kernel trace. This trace can easily represent hundreds of thousands of events per second. In this paper, we propose and evaluate a methodology, efficient algorithms, and concurrent data structures to detect and analyze latency problems that occur at the kernel level. We introduce a new kernel‐based approach that enables developers and administrators to efficiently track latency problems in production and trigger actions when abnormal conditions are detected. The result of this study is a working scalable latency tracker and an efficient approach to perform stateful tracing in production. Copyright © 2016 John Wiley & Sons, Ltd.